Detecting patterns of structure formation at various types of metal machining - Kassov, Valerij; Gribkov, Eduard; Berezshnaya, Olena; Malyhina, Svetlana; Sumets, Andrej (Eastern-European Journal of Enterprise Technologies, 2019)
This paper reports a research into influence of different types of thermal cutting, namely argon-plasma, air-plasma, and oxygen-flux cutting, on regularities in the formation of a thermal impact zone and structure formation in the cutting area. The formation of structural components of the heat-treated layers has been analyzed in detail in terms of depth of the thermal impact zone after different types of thermal cutting for steels of varying degree of doping. It was established that the result of thermal cutting is the formation of conditional sections, which are characterized by different structural components depending on the chemical composition of steels and the type of treatment. This paper describes patterns in the phase and structural transformations at thermal cutting of steels. The effect of a thermal cutting technique is shown on the formation of structural components both in the zone of melting and at sections near a main metal. The influence of the cutting technique on the depth of melted and transitional sections is given. The phenomena associated with the process of crystallization after cutting are described. The influence of cooling rate on the structure of metals in the cutting zone was considered in detail for a wide range of steel grades. The basic regularities of structure formation at the crystallization of a melted metal in the cutting zone depending on a chosen thermal cutting technique were established. The effect of a thermal cutting technique on change in the microhardness of cut surface and the depth of thermally treated layers is shown. It has been demonstrated that choosing an air-plasma-cutting method as a technological operation makes it possible to considerably reduce the depth of a thermal impact zone and microhardness in a cutting zone compared to argon-plasma and oxygen-flux cutting. The efficiency of the technological process of air-plasma cutting has been proven in comparison with other considered methods due to the reduction of depth in the thermal impact zone, which predetermines lower labor and economic expenses for the further machining of a cut surface. This reduces the production of parts and assemblies from structural steels of large thickness, for which high-performance thermal cutting is applied. Implementation of the established research results under industrial conditions would make it possible to significantly improve the efficiency and productivity of the technological process by obtaining high quality of the surface